Never let you go - Stevens, Chevy (St. Martin's Press, 2017)
"The author of Still Missing targets her readership with a novel that hits all the notes they come to expect from her--and ratchets up the stakes even more. Lindsey Nash has left an abusive relationship and her ex-husband was sent to jail. She has started over with a new life, her own business, and a teenage daughter who needs her more than ever. When her husband is finally released, Lindsey believes she has cut all ties. There is no way he can ever find her and her daughter again. But she gets the sense that someone is watching her, tracking her every move. Her new boyfriend is threatened. Her home is invaded. Even her daughter is shadowed. Lindsey is convinced it's her ex-husband, even though he claims he is a different person and doesn't want to do her any harm. But can he really change? Is the one who wants her dead even closer to home than she thought?"--